My iPad for seniors - Miller, Michael 1958- (Que, 2017)
Provides step-by-step instructions for seniors on using the iPad, covering such topics as connecting to Wi-Fi and mobile carriers, using Siri, surfing the web, sending email, installing apps, managing multimedia, and fixing common problems.